Amino-acid ester derived perylene diimides electron acceptor materials: An efficient strategy for green-solvent-processed organic solar cells. (May 2019) - Wang, Helin; Fan, Qingxuan; Chen, Lingcheng; Xiao, Yi
Abstract: We have designed and synthesized a new amino-acid ester derived ortho-ortho perylene diimides (PDI) diploid, namely oo -2PDIate, by Ullmann coupling reaction. The compound oo -2PDIate exhibits unique photophysical and electrochemical properties because of the presence of the ortho-ortho linkage and branched side chains. Moreover, the introduction of amino acid ester side chains for oo -2PDIate increases the molecular polarity and therefore making the target compound more soluble in the highly polar green solvent, which means that it can be carried out to green-solvent-processed organic solar cells as a suitable electron acceptor. By utilizing green solvent anisole as the processing solvent, the device based on oo -2PDIate as electron acceptor and PBDTTT-C as electron donor exhibits the best power conversion efficiency (PCE) of 2.24%, which is very close to the PCE (2.52%) of the device using chlorobenzene. Although the device performance is moderate, this strategy that introducing ester group side chains at the position of the imide to increase the solubility in green solvents provides an efficient way to develop PDI derivatives as the electron acceptor materials for green-solvent-processed organic solar cells (OSCs). Graphical abstract: Image 1